2016
DOI: 10.1038/nrneph.2016.87
|View full text |Cite
|
Sign up to set email alerts
|

The expanding phenotypic spectra of kidney diseases: insights from genetic studies

Abstract: Next-generation sequencing (NGS) has led to the identification of previously unrecognized phenotypes associated with classic kidney disease genes. In addition to improving diagnostics for genetically heterogeneous diseases and enabling a faster rate of gene discovery, NGS has enabled an expansion and redefinition of nephrogenetic disease categories. Findings from these studies raise the question of whether disease diagnoses should be made on clinical grounds, on genetic evidence or a combination thereof. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
83
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 156 publications
0
83
0
3
Order By: Relevance
“…Some heterozygous mutations in COL4A3 and COL4A4 genes can cause a milder phenotype, defined as thin basement membrane nephropathy (TBMN; MIM#141200, or benign familial hematuria), which is characterized by persistent microscopic hematuria although rarely combined with progressive proteinuria and end-stage renal disease [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Some heterozygous mutations in COL4A3 and COL4A4 genes can cause a milder phenotype, defined as thin basement membrane nephropathy (TBMN; MIM#141200, or benign familial hematuria), which is characterized by persistent microscopic hematuria although rarely combined with progressive proteinuria and end-stage renal disease [4]. …”
Section: Introductionmentioning
confidence: 99%
“…One mother showed focal segmental glomerulosclerosis (FSGS) on kidney biopsy. Presentation of Alport syndrome with isolated proteinuria [17] and FSGS in male and female patients [18][19][20][21] have been reported before. The etiology of FSGS may be that it develops secondary to the abnormalities in the GBM, or alternatively that FSGS belongs to a spectrum of diseases of the GBM primarily caused by a COL4A3-5 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, patients with Alport’s syndrome can present with FSGS on kidney biopsy and therefore, this cannot be used as a feature to distinguish between the two conditions [16, 17]. Mutations in the COL4A3-5 genes that encode α-chains of glomerular basement membrane collage type IV are classically associated with Alport’s syndrome, and recent studies have shown that these mutations can be associated with FSGS [18]. In our patient, whole exome sequencing did not reveal COL4A3-5 mutations.…”
Section: Discussionmentioning
confidence: 99%